Tunable Active Grounded Lossless and Lossy Inductance Simulators with Single Grounded Capacitor Using VDBAs - Worapong Tangsrirat; Wanlop Surakampontorn (My University, 2019)
In this paper, three active-C synthetic grounded inductance simulator circuits are presented, which realize tunable lossless and lossy series and parallel RL-type inductances. Each of which employs two voltage differencing buffered amplifiers (VDBAs) as active components, and a single grounded capacitor as a passive component. In all the proposed circuits, the simulated equivalent resistance and inductance values can be adjusted electronically through the transconductance gains of the VDBAs. They also do not require any critical component matching conditions and cancellation constraints. Detail non-ideal analysis including transfer errors of the VDBA has been analyzed. For circuit performance verification and comparison, some application examples are given together with computer simulation results by PSPICE program.
Keywords: Lossy compression; Equivalent series inductance; Transconductance; Component (thermodynamics); Analog and Mixed-Signal Circuit Design